2021
DOI: 10.3390/ijms22041837
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing Identifies APCDD1 and HDAC5 Genes as Potentially Cancer Predisposing in Familial Colorectal Cancer

Abstract: Germline mutations in predisposition genes account for only 20% of all familial colorectal cancers (CRC) and the remaining genetic burden may be due to rare high- to moderate-penetrance germline variants that are not explored. With the aim of identifying such potential cancer-predisposing variants, we performed whole exome sequencing on three CRC cases and three unaffected members of a Polish family and identified two novel heterozygous variants: a coding variant in APC downregulated 1 gene (APCDD1, p.R299H) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…A decrease in the expression level of PCDH20 can disrupt the integrity of the intestinal mucosa, which can contribute to the development of colitis and Crohn’s disease ( 48 ). APCDD1 (adenomatosis polyposis down-regulated 1), a negative regulator of Wnt/β-catenin pathway, its expression was regulated by promotor methylation ( 49 ). It has been demonstrated that the methylation of WNT target genes (including APCDD1) could be serve as reliable biomarkers for predicting recurrence in colon cancers ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the expression level of PCDH20 can disrupt the integrity of the intestinal mucosa, which can contribute to the development of colitis and Crohn’s disease ( 48 ). APCDD1 (adenomatosis polyposis down-regulated 1), a negative regulator of Wnt/β-catenin pathway, its expression was regulated by promotor methylation ( 49 ). It has been demonstrated that the methylation of WNT target genes (including APCDD1) could be serve as reliable biomarkers for predicting recurrence in colon cancers ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efforts to study CRC heterogeneity, our current knowledge in this field is just the tip of the iceberg. Expanding next-generation sequencing (NGS), single-cell sequencing, and whole-exome sequencing techniques along with the application of omics data at various levels, including genomics, epigenomics, transcriptomics, peptidomics, proteinomics, and metabolomics, could give us valuable information on the heterogeneity of CRCs (116)(117)(118)(119)(120)(121)(122)(123).…”
Section: Heterogeneity Assessment Methodsmentioning
confidence: 99%
“…For this purpose, we performed whole exome sequencing (WES) on a Polish family with CRC aggregation over three generations. Sequencing data of four CRC cases and two unaffected family members were subsequently analyzed using our in-house developed Familial Cancer Variant Prioritization Pipeline (FCVPPv2) which was used earlier in identification of variants and pathways involved in several familial cancers (Bandapalli et al 2018 ; Kumar et al 2018 ; Srivastava et al 2019 ; Srivastava et al 2020a ; Srivastava et al 2020b ; Skopelitou et al 2021 ; Srivastava et al 2021 ). Further in silico analyses resulted in the prioritization of a novel missense variant in the solute carrier family 15 member 4 gene ( SLC15A4 ), encoding a proton-dependent peptide/histidine transporter.…”
Section: Introductionmentioning
confidence: 99%